THE EFFECT OF PLANTING SPACE AND LEVEL OF PHOSPHOR FERTILIZER DOSE ON GROWTH, DRY MATTER YIELD, AND CRUDE PROTEIN CONTENT OF Indigofera arrecta - Akbarillah, T.; Hidayat, H. (Diponegoro University, 2010)
Study on Indigofera arrecta has not been explored widely yet. Therefore, its growth characteristicand its nutritive value need to be studied. The research was conducted to evaluate growth characteristicand its nutritive value of Indigofera arrecta planted on different planting spaces and different levels ofNPK fertilizer dose. Two factors experiments were assigned in a Split-Plot Design. The first factor (A)was planting space, (1) 50x50 cm and (2) 75x75 cm. The Second factor (B) was level of fertilizer dose,(1) 0 kg P2O5/ha+100kg K2O/ha, (2) 100kg P2O5/ha +100kg K2O kg/ha and (3) 200kg P2O5+100kgK2O/ha. The results showed that planting space had no effect on height of plant (P>0.05) but diameter ofstem were statistically different (P<0.05). In addition, their dry matter yield and crude protein contentwere not different (P>0.05) on either planting space or P fertilizer dose. There were no interactionbetween planting space and P fertilizer dose. In addition, there were no effects either planting space or Pfertilizer dose on dry matter edible part, crude protein content, and plant height. Indigofera arrectaplanted on wider planting space produce bigger stem diameter and bigger number of branch.